Upper extremity muscle force for traditional archery using Khatrah technique - Ariffin, M. S.; Sahak, R.; Rambely, A.; Zin, M. A. M. (International Journal of Advanced Trends in Computer Science and Engineering, 2020)
This study investigated the behaviour of archer's muscle in six phases of archery cycle known as stance (S), knockingarrow (NA), pre-drew (PD), full draw (FD), release (R) and follow through (FT). Firstly, muscle data atbow arm and draw arm are collected from a world class archer that performed archery with the 45lb traditional composite bow with Khatrah technique. The data are collected by using Electromyography (EMG) sensor. The sensor is placed on ten significant muscles. In order to standardise the time frame of data and suppress noise, the extracted data is normalised and smoothed respectively. Further, muscle forces are gauged and compared in each phase. Result obtained shows that high muscle force at upper and lower arm acquired at bow arm, while trunk body part for draw arm. Furthermore, using Khatrah technique, the most affected muscle is flexor carpi radialis at the bow arm. This study provides the foundation for the development of system to monitor the muscle condition of archers.